Building and Evaluating a Distributional Memory for Croatian - Šnajder, Jan (Array, 2013)
We report on the first structured distributional semantic model for Croatian, dm.hr. It is constructed after the model of the English Distributional Memory (Baroni and Lenci, 2010), from a dependency-parsed Croatian web corpus, and covers about 2M lemmas. We give details on the linguistic processing and the design principles. An evaluation shows state-of-the-art performance on a semantic similarity task with particularly good performance on nouns. The resource is freely available.